On a class of semimonotone Qo-matrices in the linear complementarity problem - Danao, Rolando A. (Operations Research Letters)
This paper is concerned with the class L* of nxn real matrices M for which the linear complementarity problem, w = Mz + q, w, O, z 0, wTz = 0, has a unique complementary solution for each q such that 0 ? q ? 0. It is shown that (a) L* lies strictly between L* and L1, the classes of strictly semimonotone and semimonotone matrices, respectively, (b) L*-matrices are Q0-matrices, and (c) L* is the largest class of Q-matrices in L*.